-2/3(6-2a)=16

Simple and best practice solution for -2/3(6-2a)=16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2/3(6-2a)=16 equation:



-2/3(6-2a)=16
We move all terms to the left:
-2/3(6-2a)-(16)=0
Domain of the equation: 3(6-2a)!=0
a∈R
We add all the numbers together, and all the variables
-2/3(-2a+6)-16=0
We multiply all the terms by the denominator
-16*3(-2a+6)-2=0
Wy multiply elements
-48a(--2=0
We use the square of the difference formula
-48a(+2=0

See similar equations:

| 5x=11−6x | | 1/2(6x+8)=25 | | 75-k=19 | | x4+5x2+4=0 | | -7x-7+8x=-8x-1 | | 4a-3=27 | | 6x+26=2x+6 | | 7x2(2x-5)=-8 | | x2-1=0 | | 5x^2+5=113 | | 52=t-5 | | 6378.1-r=2981.1 | | -w^2-4w+165=0 | | 6(2x-3)-4x=3x+12 | | -27+7x-9x=31 | | F(3)=3x^-2x+1 | | Z+(z-6)-2=-16 | | 4x-7=136 | | 83-m=31 | | 3a+8=7a | | |v+8|-5=2 | | -51+x+3x=49 | | X-5/3=4/(x-3) | | 79-b=32 | | 7-6v=-5v-8v | | 5/4x+1=1/4+1/4x | | 7x-12x-109=66 | | 58.4+s=2.6 | | 165=w^2+4w | | 4/9(2x-4=48 | | 8=17-z | | 6x−60+8x+16=180 |

Equations solver categories